Réponses

2014-03-10T21:12:33+01:00
Exercice 37
A)  x=5

A= -6x+5
A= -6(5)+5
A= -30+5
A= -25

B)  x=-2

A = -6x+5
A= -6(-2)+5
A= 12+5
A=17

C)  x= 7

A= -6x+5
A= -6(7)+5
A= -42+5
A= -37

D) x= -5

A= -6x+5
A= -6(-5)+5 
A=30+5
A= 35


La suite
a) - 5 + (- a + 2b)
a) - 5 - a + 2b
b) 9 - ( - x + 3y)
b) 9 + x - 3y
c) - a - ( - 5 + b - c)
c) - a + 5 - b + c
d) 9 + (- x2 - x + y)
d) 9 - x2 - x + y

a) 7a + ( - 5 + 2b - c)
a) 7a - 5 + 2b - c
b) - 5 - ( - x2 + 4x)
b) - 5 + x2 - 4x
c) b - ( - a + 6c - 5)
c) b + a - 6c + 5
d) - 3z + (x - y - 2)
d) - 3z + x - y - 2